Cardiovascular Abnormalities in Juvenile Dermatomyositis: A Scoping Review for the Clinical Rheumatologists - Mondal, Sanjib; Barman, Prabal; Vignesh, Pandiarajan (Frontiers in Medicine, 2022)
Juvenile dermatomyositis (JDM) is a common form of inflammatory myositis in children. Vasculopathy and endothelial dysfunction play significant roles in the pathogenesis of JDM. Cardiac involvement in JDM is often underestimated, and it may be a potential indicator of poor prognosis. Cardiac dysfunction in JDM can occur both in the acute and chronic stages of the disease. Amongst the acute complications, acute congestive heart failure (CHF), myocarditis, arrhythmia and complete heart block are common. However, these remain unrecognized due to a lack of overt clinical manifestations. Increased rates of cardiovascular abnormalities have been noted with anti-SRP and anti-Jo 1 auto-antibody positivity. Long-term follow-up studies in JDM have shown an increased prevalence of hypertension, atherosclerosis, coronary artery disease and metabolic syndrome in adolescence and adulthood. Monitoring of body-mass index, blood pressure, and laboratory evaluation of fasting glucose and lipid profile may help in identifying metabolic syndrome in children with JDM. Steroid-sparing agents, daily exercise and a healthy diet may reduce such long-term cardiac morbidities. Current use of multimodality imaging such as stress-echocardiography, contrast-enhanced echocardiography, cardiac magnetic resonance imaging, and positron emission tomography have increased the diagnostic yield of subclinical heart disease during acute and chronic stages of JDM. This review will elaborate on different aspects of cardiac dysfunction in JDM. Our review will also emphasize the importance of cardiac screening in long-term follow-up of children with JDM.